(untitled) (American Journal of Islam and Society, 1985)
Introduction This paper discusses the crisis of thought prevailing in the Muslim world today, and considers it a fundamental cause of the current degeneration, decadence and backwardness of the “Ummah.” Hopefully, it also highlights the role the International Institute of Islamic Thought will play in counteracting and ultimately overcoming the crisis. Such a theme inevitably brings the Islamic concept of knowledge to the forefront. First of all it must be decided whether such an investigation is merely an intellectual extravanganza or whether there is actually a real issue that deserves investigating. No one possessing insight into the condition of the Ummah can fail to realize that there exists a crisis involving a number of issues and complex dimensions. These issues are: 1. The backwardness of the Ummah. 2. The weakness of the Ummah. 3. The intellectual stagnation of the Ummah. 4. The absence of Ijtihad in the Ummah. 5. The absence of cultural progress in the Ummah. 6. The Ummah’s losing touch with the basic norms of Islamic civilization. All these issues indicate, in one way or the other, the intellectual crisis prevailing in the Muslim World. There is no doubt that this crisis is the cause and, at the same time, evidence of the decadence and impotence of the Ummah, and prevents it from anything significant to the culture and civilization of the modern world. This incapability is futher exacerbated by the frequency of political, economic and military crises ...